Association Between the Gut Microbiome and Their Metabolites With Human Blood Pressure Variability. Issue 8 (8th June 2022) - Dinakis, Evany; Nakai, Michael; Gill, Paul; Ribeiro, Rosilene; Yiallourou, Stephanie; Sata, Yusuke; Muir, Jane; Carrington, Melinda; Head, Geoffrey A.; Kaye, David M.; Marques, Francine Z.
Abstract : Background: Blood pressure (BP) variability is an independent risk factor for cardiovascular events. Recent evidence supports a role for the gut microbiota in BP regulation. However, whether the gut microbiome is associated with BP variability is yet to be determined. Here, we aimed to investigate the interplay between the gut microbiome and their metabolites in relation to BP variability. Methods: Ambulatory BP monitoring was performed in 69 participants from Australia (55.1% women; mean±SD, 59.8±7.26 years; body mass index, 25.2±2.83 kg/m 2 ). These data were used to determine nighttime dipping, morning BP surge (MBPS) and BP variability as SD. The gut microbiome was determined by 16S ribosomal RNA (rRNA) sequencing and metabolite levels by gas chromatography. Results: We identified specific taxa associated with systolic BP variability, nighttime dipping, and MBPS. Notably, Alistipesfinegoldii and Lactobacillus spp. were only present in participants within the normal ranges of BP variability, MBPS and dipping, while Prevotella spp. and Clostridium spp., were found to be present in extreme dippers and the highest quartiles of BP SD and MBPS. There was a negative association between MBPS and microbial α-diversity (r=−0.244, P =0.046). MBPS was also negatively associated with plasma levels of microbial metabolites called short-chain fatty acids (r=−0.305, P =0.020), particularly acetate (r=−0.311, P =0.017). Conclusions: Gut microbiome diversity, levels of microbial metabolites, and the bacteria Alistipesfinegoldii and Lactobacillus were associated with lower BP variability and Clostridium and Prevotella with higher BP variability. Thus, our findings suggest the gut microbiome and metabolites may be involved in the regulation of BP variability.